Impact of Destination Image Formation on Tourist Trust: Mediating Role of Tourist Satisfaction - Jebbouri, Abdelhamid; Zhang, Heqing; Imran, Zahid; Iqbal, Javed; Bouchiba, Nasser (Frontiers in Psychology, 2022)
Tourist destinations with cultural heritage have arisen as a prominent issue in tourism literature. Creating a positive image of the destination can influence tourists' satisfaction and willingness to return. The goal of this research is to investigate the relationship between destination image formation (DIF), tourist satisfaction (TS), and tourist trust (TT). As a result, the structural relationships between local community participation, (LCP) authenticity (A), access to local products (ALP), TS, and TT were investigated in this study. This study used a quantitative approach based on a survey of 644 domestic and foreign tourists visiting the Guangdong cities of Guangzhou, Foshan, and Shenzhen. The statistical software SmartPLS 3.3.3 was used to determine the relationship between variables in the research model using structural equation modeling. The outcomes show a positive correlation between LCP, A, and ALP, which led to tourist satisfaction and, eventually, tourist trust. It is concluded that the DIF and TS may result in increased tourist trust. There is also a discussion of additional theoretical contributions, practical implications, and limitations. The outcomes of this study will help to shed light on the variables that encourage and promote tourism in developing countries.